Additive for building ceramic production and ceramic dry preparation method
By using additives composed of calcium lignosulfonate and glycerol in ceramic production and using dry preparation method to treat lithium slag or red mud, the problem of difficulty in effectively utilizing these solid wastes in traditional wet processes is solved, and the quality of ceramic products and the efficient utilization of solid waste is achieved.
Patent Information
- Application Number
- CN202510086747.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-20
- Publication Date
- 2025-04-15
AI Technical Summary
Traditional wet process is difficult to effectively utilize lithium slag and red mud, resulting in a decline in the quality of ceramic products, and insufficient recycling of lithium slag and red mud, causing environmental pollution.
Using an additive for the production of architectural ceramics, consisting of calcium lignosulfonate and glycerin, lithium slag or red mud is treated by dry preparation method, including formula selection, stirring and mixing, grinding and drying, sieving, granulation and firing.
Through the dry preparation method, we ensure that the powder granules grading meets the standards, improve powder fluidity and press fabric uniformity, avoid cracking of ceramic products, and increase the utilization rate of lithium slag and red mud, and reduce production costs.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of ceramic production, and in particular relates to an additive for producing building ceramics and a ceramic dry preparation method. Background Art
[0002] With the rapid development of lithium-ion battery new energy, the demand for lithium is increasing. Lithium extraction from lithium mica has become an indispensable part of the development of lithium-ion battery new energy. The process of lithium extraction from lithium mica is to crush the lithium mica first and then extract lithium. The process will produce solid waste lithium slag, which occupies a lot of land. With the development of the lithium industry, the output of lithium slag increases, and a lot of land is needed to pile up these waste slags. Lithium slag will cause environmental pollution. Lithium slag may contain harmful substances such as heavy metals. If these substances enter the soil, they will cause soil pollution, reduce soil fertility and deteriorate soil quality. If harmful substances flow into water bodies under conditions such as rain erosion, they will cause water pollution, affect the survival of aquatic organisms, and may be enriched through the food chain, eventually causing harm to human health. The recycling of lithium slag is urgent.
[0003] Red mud is the mud residue produced by leaching alumina from bauxite with strong alkali. Generally, for every ton of alumina produced, 0.6 to 2.0 tons of red mud are produced. my country discharges about 2 million tons of red mud every year. The large amount of red mud discharge not only occupies a large amount of land and arable land, but also requires huge investment in the construction and maintenance of storage yards. Red mud contains highly alkaline substances, which penetrate into the surrounding area and groundwater, causing pollution of land and water resources. At the same time, the red mud in the storage yard is dried, and the dust formed is flying everywhere, causing ecological pollution. Therefore, the recycling of red mud has become a key task to be considered at present.
[0004] After analyzing the performance indicators of lithium slag and red mud, it was found that the chemical element indicators of lithium slag and red mud are consistent with the mechanism of building ceramic formula, but the traditional wet process uses ball milling slurry to produce building ceramics, and the particle size distribution of lithium slag may not be suitable. If the particle size of lithium slag is too coarse, it cannot be well mixed with other raw materials during the ball milling process, which will affect the uniformity of ceramic raw materials, and then lead to a decrease in the quality of ceramic products, such as uneven density. If the particle size is too fine, agglomeration may occur, which is also not conducive to uniform mixing with other ceramic raw materials, and will affect the ball milling efficiency. The pH value of lithium slag may also be a factor. If the lithium slag itself is acidic or alkaline, it will change the overall pH environment of the slurry, causing the surface suction and repulsion of the colloid particles to lose balance, causing the slurry to flocculate and be unable to flow, so the traditional wet process cannot effectively consume solid waste lithium slag.
[0005] As for red mud, since it contains a large amount of alkaline substances such as calcium oxide and sodium oxide, the pH value is generally between 10-12, which is strongly alkaline. It will change the chemical environment of the mud and change the surface charge distribution of clay particles in the mud, thereby affecting the interaction force between particles, which may cause particle agglomeration or dispersion, and ultimately affect the fluidity of the mud, resulting in the inability to degelatinize and the inability to produce normally.
[0006] However, if lithium slag or red mud is directly used to prepare building ceramics by dry method, due to the physical and chemical properties of lithium slag or red mud, powder particles are not easy to form during the granulation process, or the formed powder particles have poor fluidity, resulting in uneven powder during the spreading process, causing the final prepared ceramic product to have quality problems such as cracking. Summary of the invention
[0007] The present invention overcomes the shortcomings of the prior art and provides an additive for the production of building ceramics and a ceramic dry preparation method; it solves the problem that when directly using lithium slag or red mud to prepare building ceramics by a dry method, powder particles are not easy to form during the granulation process, or the formed powder particles have poor fluidity, resulting in uneven powder during the distribution process.
[0008] The present invention is achieved through the following technical solutions: An additive for producing building ceramics, comprising 80% to 90% by mass of calcium lignosulfonate and 10% to 20% by mass of glycerol.
[0009] Preferably, it is composed of 80% by mass of calcium lignosulfonate and 20% by mass of glycerol.
[0010] A ceramic dry preparation method comprises the following steps: S1. Selecting raw materials for producing building ceramics by chemical analysis of the formula; the raw materials include lithium slag or red mud; S2, mixing the raw materials according to the formula ratio, and stirring and mixing to obtain a formula mixed material; S3, grinding and drying the formula mixture to make dry powder; S4, sieving the dry powder to obtain 60-120 mesh sieved dry powder; S5, the sieved dry powder is atomized and granulated by a granulator to prepare a powder with a water content of 7.0% to 8.5% by weight; 1% to 5% by weight of an additive is added to the water of the atomized granulation; the additive is an additive for the production of building ceramics as described in claim 1 or 2; The particle size distribution of the powder is in the following range: Above 20 mesh ≤5%, 20 mesh-40 mesh 10%--30%, 40 mesh-60 mesh 20%-70%, 60 mesh-80 mesh 10%-50%, 80 mesh-100 mesh 10%-20%, below 100 mesh ≤1%; S6. Spread, press, dry and burn the powder.
[0011] Preferably, when the raw material contains lithium slag, the mass percentage of the lithium slag is 1%-60%; when the raw material contains red mud, the mass percentage of the red mud is 10%-60%.
[0012] Preferably, the firing temperature is 1080° C. to 1240° C., and the firing period is 10 min to 60 min.
[0013] Preferably, in step S6, the dried green body is glazed and printed on a glaze line and then sent into a kiln for firing.
[0014] Preferably, 3% by weight of additives are added to the water for atomization granulation.
[0015] Preferably, the dry powder described in step S3 has a fineness of 200-600 mesh and a moisture content of ≤3%.
[0016] The beneficial effects of the present invention compared with the prior art are as follows: The additive for building ceramic production described in the invention can ensure that the granulated powder reaches the standard particle gradation through the specific formula of calcium wood sulfonate and glycerol, which is helpful for the formation of powder particles in the granulation process, enhances the fluidity of the powder, and evenly distributes the material on the press, thereby achieving the requirement of producing building ceramics without cracking.
[0017] By adding a specific proportion of calcium lignosulfonate and glycerol during the granulation process, the proportion of solid waste such as lithium slag or red mud in the preparation of raw materials can be increased, which effectively improves the utilization rate of solid waste and reduces production costs. DETAILED DESCRIPTION
[0018] In order to make the technical problems, technical solutions and beneficial effects to be solved by the present invention clearer, the present invention is further described in detail in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention. The technical solutions of the present invention are described in detail below in conjunction with the embodiments, but the scope of protection is not limited thereto.
[0019] Example 1 This embodiment proposes a dry preparation method for producing architectural ceramics using lithium slag, which specifically comprises the following steps: S1. Formula selection: production of 800*800 glazed tiles, water absorption rate ≤3%; The composition of lithium slag is as follows: Chemical composition of green gangue: Chemical composition of bentonite: Chemical composition of sand and gangue: According to the chemical composition, physical indexes and product quality standards of the selected raw materials, the mass percentage of each raw material in the formula is determined as follows: lithium slag: 40%, bentonite: 22%, sand gangue: 25%, green gangue: 13%; The calculated formula ingredients are as follows: Through chemical analysis of the formula, its composition meets the requirements of the produced product.
[0020] S2. Each of the above raw materials is accurately batched according to the formula ratio through an automatic batching machine, sent to the mixing bin for uniform mixing to obtain the formula mixture, and then sent to the transfer bin for standby use.
[0021] S3. The formula mixture in the transfer bin is fed into the vertical mill through automatic feeding equipment for grinding and drying to make dry powder for storage. The detection standard of dry powder is: fineness is 250 mesh, moisture ≤3%; no debonding agent is needed, and the strong acidity and alkalinity of lithium slag does not affect the normal powder making of the vertical mill; vertical mill grinding and drying equipment is used to make dry powder, which solves the problem that lithium slag cannot be debonded in wet ball mill slurry.
[0022] S4. The dry powder in the dry powder bin is filtered through a 120-mesh fully automatic ultrasonic oscillating screen. The filtered dry powder enters the granulation transfer bin through the powder conveying system for standby use; the fully automatic ultrasonic oscillating screen ensures the filtering of impurities and other organic matter and the pass rate of dry powder screening, ensuring that ceramic products are fired without pits, bulges, and cracks.
[0023] S5. Add 1% additive to the water used for granulation. The additive ingredients are 80% calcium xanthate and 20% glycerol. The dry powder in the transfer warehouse is made into 8.0% moisture powder through the principle of atomized water droplets and powder-in-water in the flotation granulator and sent to the press warehouse for standby. The particle size distribution of the powder is as follows: The function of the additive is to ensure the formation of powder particles during the granulation process, enhance the fluidity of the powder, ensure uniform distribution of the press, and prevent the bricks from cracking.
[0024] S6. The powder is spread and pressed through a press and then enters a drying kiln for drying.
[0025] S7. After drying, the body is subjected to base glaze, inkjet printing and polishing glaze through the glaze line and then enters the kiln for firing.
[0026] S8. The green body is fired at high temperature in a kiln to form a ceramic semi-finished product. The kiln length is 200 meters, the firing temperature is 1190°C, and the firing cycle is 50 minutes.
[0027] S9. After firing, the semi-finished products are polished, edged, packaged and stored.
[0028] Example 2 This embodiment proposes a dry preparation method for producing architectural ceramics using lithium slag, which specifically comprises the following steps: S1. Formula selection; production of 300*600 interior wall tiles, water absorption rate 6%--10%; The composition of lithium slag is as follows: Chemical composition of green gangue: Chemical composition of sand and gangue: According to the chemical composition, physical indexes and product quality standards of the selected raw materials, the proportion of each raw material in the formula is determined: lithium slag: 10%, sand gangue: 65%, green gangue: 25% The calculated formula ingredients are as follows: Through chemical analysis of the formula, its composition meets the requirements of the produced product.
[0029] S2. Each of the above raw materials is accurately batched according to the formula ratio through an automatic batching machine, sent to the mixing bin for uniform mixing to obtain the formula mixture, and then sent to the transfer bin for standby use.
[0030] S3. The formula mixture in the transfer bin is fed into the vertical mill through automatic feeding equipment, ground and dried, and then made into dry powder for storage; the detection standard of dry powder is: fineness is 200 mesh, moisture ≤3%; the strong acidity and alkalinity of lithium slag does not affect the normal powder making of the vertical mill.
[0031] S4. The dry powder in the dry powder bin is filtered through an 80-mesh fully automatic ultrasonic oscillating screen. The filtered dry powder enters the granulation transfer bin through the powder conveying system for standby use; the characteristic fully automatic ultrasonic oscillating screen ensures the filtering of impurities and other organic matter and the pass rate of dry powder screening, ensuring that ceramic products are fired without pits, bulges, and cracks.
[0032] S5. Add 3% additives to the water used for granulation. The additive ingredients are 80% calcium xanthate and 20% glycerol. The dry powder in the transfer warehouse is made into 7.6% moisture powder through the principle of atomized water droplets and powder-in-water in the flotation granulator and sent to the press warehouse for standby. The particle size distribution of the powder is as follows: The function of the additive is to ensure the formation of powder particles during the granulation process, enhance the fluidity of the powder, ensure uniform distribution of the press, and prevent the bricks from cracking.
[0033] S6. The powder is fed through a press, pressed, and then sent to a drying kiln for drying and then sent to a biscuit kiln for firing at 900°C.
[0034] S7. After firing, the blank is passed through the glaze line for base glaze, inkjet printing, and protective glaze before entering the kiln for firing.
[0035] S8. The green body is fired in a kiln at high temperature to form a ceramic semi-finished product. The kiln length is 200 meters, the firing temperature is 1100°C, and the firing cycle is 20 minutes.
[0036] S9. After firing, the semi-finished products are edged, packaged and stored.
[0037] Example 3 This embodiment proposes a dry preparation method for producing architectural ceramics using lithium slag, which specifically comprises the following steps: S1. Formula and material selection; production of 300*600 paving stones with a water absorption rate of 3%--6%.
[0038] The composition of lithium slag is as follows: Chemical composition of potassium feldspar: Chemical composition of bentonite: Chemical composition of sand and gangue: According to the chemical composition, physical indexes and product quality standards of the selected raw materials, the proportion of each raw material in the formula is determined: lithium slag: 60%, sand and gangue: 14%, potassium feldspar: 10%, bentonite: 16%; The calculated formula ingredients are as follows: Through chemical analysis of the formula, its composition meets the requirements of the produced product.
[0039] The selected raw materials for producing building ceramics are lithium slag, bentonite, potassium feldspar and sand gangue.
[0040] S2. Each of the above raw materials is accurately batched according to the formula ratio through an automatic batching machine, sent to the mixing bin for uniform mixing to obtain the formula mixture, and then sent to the transfer bin for standby use.
[0041] S3. The formula mixture in the transfer bin is fed into the vertical mill through automatic feeding equipment, ground and dried, and then stored as dry powder; the detection standard of dry powder is: fineness is 250 mesh, moisture ≤3%; no debonding agent is needed, and the strong acidity and alkalinity of lithium slag does not affect the normal powder making of the vertical mill.
[0042] S4. The dry powder in the dry powder bin is filtered through a 60-mesh fully automatic ultrasonic oscillating screen. The filtered dry powder enters the granulation transfer bin through the powder conveying system for standby use; the characteristic fully automatic ultrasonic oscillating screen ensures the filtering of impurities and other organic matter and the pass rate of dry powder screening, ensuring that the ceramic products are fired without pits, bulges, cracks and defects.
[0043] S5. Add 5% additives to the water used for granulation. The additive ingredients are 80% calcium xanthate and 20% glycerol. The dry powder in the transfer warehouse is made into 7.8% moisture powder through the principle of atomized water droplets and powder-in-water in the flotation granulator and sent to the press warehouse for standby. The particle size distribution of the powder is as follows: The function of the additive is to ensure the formation of powder particles during the granulation process, enhance the fluidity of the powder, ensure uniform distribution of the press, and prevent the bricks from cracking.
[0044] S6. The powder is spread and pressed through a press and then enters a drying kiln for drying.
[0045] S7. After drying, the green body is glazed and printed on the glaze line and then sent into the kiln for firing.
[0046] S8. The green body is fired at high temperature in a kiln to form a ceramic semi-finished product. The kiln length is 200 meters, the firing temperature is 1140°C, and the firing cycle is 35 minutes.
[0047] S9. After firing, the semi-finished products are edged, packaged and stored.
[0048] Example 4 This embodiment proposes a dry preparation method for producing building ceramics using red mud, which specifically comprises the following steps: S1. Formula selection; production of 800*800 glazed tiles, water absorption rate ≤3% The composition of red mud is as follows: Chemical composition of green gangue: Chemical composition of bentonite: Chemical composition of sand and gangue: According to the chemical composition, physical indexes and product quality standards of the selected raw materials, the proportion of each raw material in the formula is determined as follows: red mud: 12%, bentonite: 18%, sand gangue: 50%, green gangue: 20%; The calculated formula ingredients are as follows: Through chemical analysis of the formula, its composition meets the requirements of the produced product.
[0049] Red mud, green gangue, bentonite and silica sand are selected as raw materials for producing building ceramics.
[0050] S2. Each of the above raw materials is accurately batched according to the formula ratio through an automatic batching machine, sent to the mixing bin for uniform mixing to obtain the formula mixture, and then sent to the transfer bin for standby use.
[0051] S3. The formula mixture in the transfer bin is fed into the vertical mill through the automatic feeding equipment, ground and dried, and then stored as dry powder; the testing standard of dry powder is: fineness is 250 mesh, moisture ≤3%; no debonding agent is needed, and the strong alkalinity of red mud does not affect the normal powder making of the vertical mill. The vertical mill grinding and drying equipment is used to make dry powder, which solves the problem that red mud cannot be debonded in wet ball mill mud.
[0052] S4. The dry powder in the dry powder bin is filtered through a 120-mesh fully automatic ultrasonic oscillating screen. The filtered dry powder enters the granulation transfer bin through the powder conveying system for standby use; the characteristic fully automatic ultrasonic oscillating screen ensures the filtering of impurities and other organic matter and the pass rate of dry powder screening, ensuring that ceramic products are fired without pits, bulges, and cracks.
[0053] S5. Add 1% additive to the water used for granulation. The additive ingredients are 80% calcium xanthate and 20% glycerol. The dry powder in the transfer warehouse is made into 8.0% moisture powder through the principle of atomized water droplets and powder-in-water in the flotation granulator and sent to the press warehouse for standby. The particle size distribution of the powder is as follows: The function of the additive is to ensure the formation of powder particles during the granulation process, enhance the fluidity of the powder, ensure uniform distribution of the press, and prevent the bricks from cracking.
[0054] S6. The powder is spread and pressed through a press and then enters a drying kiln for drying.
[0055] S7. After drying, the body is subjected to base glaze, inkjet printing and polishing glaze through the glaze line and then enters the kiln for firing.
[0056] S8. The green body is fired at high temperature in a kiln to form a ceramic semi-finished product. The kiln length is 200 meters, the firing temperature is 1120°C, and the firing cycle is 55 minutes.
[0057] S9. After firing, the semi-finished products are polished, edged, packaged and stored.
[0058] Example 5 This embodiment proposes a dry preparation method for producing building ceramics using red mud, which specifically comprises the following steps: S1. Formula selection; production of 300*600 interior wall tiles, water absorption rate 6%--10%; The composition of red mud is as follows: Chemical composition of green gangue: Chemical composition of sand and gangue: According to the chemical composition, physical indexes and product quality standards of the selected raw materials, the proportion of each raw material in the formula is determined: red mud: 40%, sand gangue: 40%, green gangue: 20% The calculated formula ingredients are as follows: Through chemical analysis of the formula, its composition meets the requirements of the produced product.
[0059] Red mud, green gangue and sand gangue are selected as raw materials for producing building ceramics.
[0060] S2. Each of the above raw materials is accurately batched according to the formula ratio through an automatic batching machine, sent to the mixing bin for uniform mixing to obtain the formula mixture, and then sent to the transfer bin for standby use.
[0061] S3. The formula mixture in the transfer bin is fed into the vertical mill through automatic feeding equipment, ground and dried, and then stored as dry powder. The detection standard of dry powder is: fineness of 200 mesh, moisture ≤3%; no degumming agent is needed, and the strong alkalinity of red mud does not affect the normal powder making of the vertical mill.
[0062] S4. The dry powder in the dry powder bin is filtered through an 80-mesh fully automatic ultrasonic oscillating screen. The filtered dry powder enters the granulation transfer bin through the powder conveying system for standby use; the characteristic fully automatic ultrasonic oscillating screen ensures the filtering of impurities and other organic matter and the pass rate of dry powder screening, ensuring that ceramic products are fired without pits, bulges, and cracks.
[0063] S5. Add 3% additives to the water used for granulation. The additive ingredients are 80% calcium xanthate and 20% glycerol. The dry powder in the transfer warehouse is made into 7.6% moisture powder through the principle of atomized water droplets and powder-in-water in the flotation granulator and sent to the press warehouse for standby. The particle size distribution of the powder is as follows: The function of the additive is to ensure the formation of powder particles during the granulation process, enhance the fluidity of the powder, ensure uniform distribution of the press, and prevent the bricks from cracking.
[0064] S6. The powder is fed through a press, pressed, and then sent to a drying kiln for drying and then sent to a biscuit kiln for firing at 900°C.
[0065] S7. After firing, the blank is passed through the glaze line for base glaze, inkjet printing, and protective glaze before entering the kiln for firing.
[0066] S8. The green body is fired in a kiln at high temperature to form a ceramic semi-finished product. The kiln length is 200 meters, the firing temperature is 1100°C, and the firing cycle is 20 minutes.
[0067] S9. After firing, the semi-finished products are edged, packaged and stored.
[0068] Example 6 This embodiment proposes a dry preparation method for producing building ceramics using red mud, which specifically comprises the following steps: S1. Formula and material selection; production of 300*600 paving stones with a water absorption rate of 3%--6%.
[0069] The composition of red mud is as follows: Chemical composition of green gangue: Chemical composition of silica sand: According to the chemical composition, physical indexes and product quality standards of the selected raw materials, the proportion of each raw material in the formula is determined: red mud: 58%, silica sand: 35%, green gangue: 5%; The calculated formula ingredients are as follows: Through chemical analysis of the formula, its composition meets the requirements of the produced product.
[0070] Red mud, green gangue and silica sand are selected as raw materials for producing building ceramics.
[0071] S2. Each of the above raw materials is accurately batched according to the formula ratio through an automatic batching machine, sent to the mixing bin for uniform mixing to obtain the formula mixture, and then sent to the transfer bin for standby use.
[0072] S3. The formula mixture in the transfer bin is fed into the vertical mill through automatic feeding equipment, ground and dried, and then stored as dry powder. The detection standard of dry powder is: fineness of 200 mesh, moisture ≤3%; no degumming agent is needed, and the strong alkalinity of red mud does not affect the normal powder making of the vertical mill.
[0073] S4. The dry powder in the dry powder bin is filtered through a 60-mesh fully automatic ultrasonic oscillating screen. The filtered dry powder enters the granulation transfer bin through the powder conveying system for standby use; the characteristic fully automatic ultrasonic oscillating screen ensures the filtering of impurities and other organic matter and the pass rate of dry powder screening, ensuring that the ceramic products are fired without pits, bulges, cracks and defects.
[0074] S5. Add 5% additives to the water used for granulation. The additive ingredients are 80% calcium xanthate and 20% glycerol. The dry powder in the transfer warehouse is made into 7.8% moisture powder through the principle of atomized water droplets and powder-in-water in the flotation granulator and sent to the press warehouse for standby. The particle size distribution of the powder is as follows: The function of the additive is to ensure the formation of powder particles during the granulation process, enhance the fluidity of the powder, ensure uniform distribution of the press, and prevent the bricks from cracking.
[0075] S6. The powder is spread and pressed through a press and then enters a drying kiln for drying.
[0076] S7. After drying, the green body is glazed and printed on the glaze line and then sent into the kiln for firing.
[0077] S8. The green body is fired at high temperature in a kiln to form a ceramic semi-finished product. The kiln length is 200 meters, the firing temperature is 1140°C, and the firing cycle is 35 minutes.
[0078] S9. After firing, the semi-finished products are edged, packaged and stored.
[0079] Experimental Example 1 The following is based on experimental data to verify the effect of additives on powder particle size distribution; The following table shows the standard particle size distribution of powder materials: The experiment added 3% additives to the granulation water to test the effects of different additive components on the particle size distribution of the granulation powder: The experimental additives are 80% calcium lignosulfonate and 20% glycerol. The effect of the proportion of additives added to granulation water on the particle size distribution of the powder is as follows: According to the comparison of the above two experiments, the additive ingredients are 80% calcium wood sulfonate and 20% glycerol, and the addition ratio is 1%-5%, which ensures that the granulated powder reaches the standard particle grading and meets the requirement of producing building ceramics without cracking.
[0080] The above content is a further detailed description of the present invention in combination with a specific preferred embodiment. It cannot be determined that the specific embodiments of the present invention are limited to this. For ordinary technicians in the technical field to which the present invention belongs, several simple deductions or substitutions can be made without departing from the present invention, which should be regarded as belonging to the present invention and the scope of patent protection determined by the submitted claims.
Claims
1. An additive for the production of building ceramics, characterized in that: It is composed of 80% to 90% by mass of calcium lignosulfonate and 10% to 20% by mass of glycerol.
2. An additive for building ceramic production according to claim 1, characterized in that: It is composed of 80% calcium lignosulfonate and 20% glycerol by mass.
3. A ceramic dry preparation method, characterized in that: The following steps are involved: S1. Selecting raw materials for producing building ceramics by chemical analysis of the formula; the raw materials include lithium slag or red mud; S2, mixing the raw materials according to the formula ratio, and stirring and mixing to obtain a formula mixed material; S3, grinding and drying the formula mixture to make dry powder; S4, sieving the dry powder to obtain 60-120 mesh sieved dry powder; S5, the sieved dry powder is atomized and granulated by a granulator to prepare a powder with a water content of 7.0% to 8.5% by weight; 1% to 5% by weight of an additive is added to the water of the atomized granulation; the additive is an additive for the production of building ceramics as described in claim 1 or 2; The particle size distribution of the powder is in the following range: Above 20 mesh ≤5%, 20 mesh-40 mesh 10%--30%, 40 mesh-60 mesh 20%-70%, 60 mesh-80 mesh 10%-50%, 80 mesh-100 mesh 10%-20%, below 100 mesh ≤1%; S6. Spread, press, dry and burn the powder.
4. A ceramic dry preparation method according to claim 3, characterized in that: When the raw material contains lithium slag, the mass percentage of the lithium slag is 1%--60%; when the raw material contains red mud, the mass percentage of the red mud is 10%--60%.
5. A ceramic dry preparation method according to claim 3, characterized in that: The firing temperature is 1080° C. to 1240° C., and the firing period is 10 min to 60 min.
6. A ceramic dry preparation method according to claim 3, characterized in that: In step S6, the dried green body is glazed and printed on a glaze line and then sent into a kiln for firing.
7. A ceramic dry preparation method according to claim 3, characterized in that: Add 3% by weight of additives to the water used for atomization granulation.
8. A ceramic dry preparation method according to claim 3, characterized in that: The dry powder described in step S3 has a fineness of 200-600 mesh and a moisture content of ≤3%.